Analgesic effect of subcutaneous injection of different concentrations of methylene blue after hemorrhoidectomy: A retrospective study - Long, Qing; Li, Jun; Li, Yan (Frontiers in Surgery, 2023)
Objective: Subcutaneous injection of methylene blue around the anus may help reduce postoperative pain. However, the concentration of methylene blue is still controversial. Therefore, Our study aims to investigate the efficacy and safety of different methylene blue injected concentrations subcutaneously in pain treatment after hemorrhoidectomy. Methods: A total of 180 consecutive patients with grade III or IV hemorrhoids from March 2020 to December 2021 were reviewed. All patients underwent hemorrhoidectomy under spinal anesthesia and were divided into three groups. Group A received subcutaneous injection of 0.1% methylene blue after hemorrhoidectomy, group B received subcutaneous injection of 0.2% methylene blue, and Group C did not received subcutaneous injection of methylene blue. The primary outcome measures were the visual analog scale (VAS) pain score on postoperative days 1, 2, 3, 7, 14, and total analgesic consumption within 14 days. Secondary outcomes were complications after hemorrhoidectomy, including acute urinary retention, secondary bleeding, perianal incision edema, and perianal skin infection, and the Wexner scores used to assess the level of anal incontinence at one and three months after surgery. Results: There was no significant difference among three groups in sex, age, course of the disease, hemorrhoid grade and the number of incisions, and there was no significant difference in the volume of methylene blue injected between group A and group B. The VAS pain score and total analgesics consumption within 14 days in group A and group B were significantly lower than those in group C, but the differences between group A and group B were not statistically significant. The Wexner scores of group B were significantly higher than those of group A and group C one month after the operation, but the differences between group A and group C were not statistically significant. In addition, the Wexner score among three groups decreased to zero at three months after operation. There was no significant difference in the incidence of other complications among three groups. Conclusion: The perianal injection of 0.1% methylene blue and 0.2% methylene blue have a similar analgesic effect in pain treatment after hemorrhoidectomy, but 0.1% methylene blue has higher safety.